Forewarning of the Persuasive Attempt in Advertising Contexts - Briñol, Pablo; Cárdaba, Miguel-Angel; Gallardo, Ismael; Horcajo, Javier (Anales de Psicología / Annals of Psychology, 2014)
Forewarning of a persuasive attempt has been found to reduce persuasion because people tend to resist being manipulated. Likewise, messages that are high in ambiguity tend to be less persuasive than messages that are clear, among other reasons, because people prefer information that is easy to be processed. The present research postulates that these two variables (persuasive attempt forewarning and message ambiguity) can result paradoxically persuasive when combined together. Participants of the present experiment received a message composed by images that were presented in a logic (low ambiguity) or in a random order (high ambiguity). Furthermore, the message was said to be a commercial advertisement or a neutral narrative. As predicted, it was found that the highly ambiguous message was more persuasive when it was presented as an advertisement rather than as a narrative context. Paradoxically, knowing that the message constitutes a persuasive attempt (ad) could bias the generation of thoughts to interpret that information in a positive manner (consonant with the direction of the arguments supposedly contained in the ad), leading to more attitude change.